Analytical evaluation of local effects in cylindrical shells testing and design - Guarracino, F. (Проблемы прочности, 2009)
A simple analytical evaluation of apparently anomalous results from tests on circular cylindrical shells that have been observed in the past is provided on the basis of the classical Ritz approach and modified Donnell relationships. Із використанням класичного підходу Рітца та модифікованих рівнянь Доннелла виконано просту аналітичну оцінку явно аномальних результатів, які отримані при випробуваннях круглих циліндричних оболонок. С использованием классического подхода Ритца и модифицированных уравнений Доннелла выполнена простая аналитическая оценка явно аномальных результатов, полученных при испытаниях круглых цилиндрических оболочек.